OPSI SAHAM PADA PASAR MODAL DI INDONESIA (STUDI PASAR OPSI SAAT PASAR OPSI MASIH BERLANGSUNG DI BURSA EFEK INDONESIA) - Dewi, Syanti; Ramli, Ishak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2018)
Stock option exchange market is not working anymore in the Indonesian Stock Exchange, using the data option exchange market for the running period 2007-2008, we analyzed the effect of stock price, strike price, time to maturity, volatility and risk- free interest rate on the stock option’s price of listed stock call or put option trading at the Indonesian Stock Exchange during 2007-2008. The results found that the stock price, strike price, time to maturity, volatility and risk-free interest rate are positive significantly affecting the stock option price either the buying option price or the selling option price in Indonesia Stock Exchange 2007-2008 period. While there were no variables that significantly affected the call option during the periode 2007-2008, furthermore stock prices and strike prices significantly affected the put option prices. Time to maturity, Volatility, and risk free interest rate did not significantly affect the put option prices.That is why the stock option exchange market stop since the investor were not sure to the stock option price versus the risk of the volatility, time to maturity, and riskfree rate.The stock options exchange market ceases to function at the Indonesia Stock Exchange, using the data option exchange market for the 2007-2008 period, we analyze the effect of stock prices, strike prices, maturity time, volatility and risk-free interest rates. at the price of stock options from the call of listed shares or put option trading on the Indonesia Stock Exchange during 2007-2008. The result found that the stock price, strike price, maturity, volatility and risk-free interest rates significantly and positively affect the price of stock options in either the purchase option price or selling option prices at the Indonesia Stock Exchange for the 2007-2008 period. While there are no variables that significantly affect call options during the 2007-2008 period, further stock prices and strike prices significantly affect the purchase option price. Time for maturity, volatility and risk-free interest rates do not significantly affect the put option price. That is the reason why the stock options exchange market ceases, because investors are unsure of stock option prices versus volatility risks, time until maturity, and risk free rates.Keywords : Stock Options, Share Price, Stock Options Price, Volatility.